1999
DOI: 10.1046/j.1523-1755.1999.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin IV stimulates plasminogen activator inhibitor-1 expression in proximal tubular epithelial cells

Abstract: Our results demonstrate that Ang II stimulates PAI-1 mRNA expression and the production of its protein in human proximal tubular cells. This is mainly-if not exclusively-due to Ang IV, which acts on a receptor that is different than AT1 or AT2. Therefore, it can be hypothesized that the induction of PAI-1 by Ang IV may be implicated in the pathogenesis of renal interstitial fibrosis in several forms of chronic glomerulonephritides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
66
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 58 publications
5
66
0
2
Order By: Relevance
“…These results are in contrast to those of other studies, which have suggested that the effects of Ang II are mediated by an Ang IV/AT 4 pathway. 24 The complete blockade of Ang II-induced PAI-1 expression by the AT 1 -selective antagonist candesartan may be attributed to its higher ) and/or candesartan (25 g ⅐ kg Ϫ1 ⅐ min…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in contrast to those of other studies, which have suggested that the effects of Ang II are mediated by an Ang IV/AT 4 pathway. 24 The complete blockade of Ang II-induced PAI-1 expression by the AT 1 -selective antagonist candesartan may be attributed to its higher ) and/or candesartan (25 g ⅐ kg Ϫ1 ⅐ min…”
Section: Discussionmentioning
confidence: 99%
“…9 In contrast, other reports have suggested that the AT 1 receptor does not mediate Ang II-stimulated PAI-1 expression. 24,25 Establishing the role of the AT 1 receptor in the regulation of PAI-1 expression may have important clinical significance related to potential differences between ACE inhibitors and AT 1 antagonists on the fibrinolytic system.…”
mentioning
confidence: 99%
“…PAI-1, u-PA, and TGF-␤ mRNA levels were studied by Northern blotting as described previously (40). Briefly, electrophoresis of 20 g of total RNA from each experimental condition was carried out in 1% agarose gel with 2.2 M formaldehyde.…”
Section: Northern Blottingmentioning
confidence: 99%
“…The membrane was stained with ethidium bromide to evaluate the 28S and 18S ribosomal bands and prehybridized at 42°C for 2 h in 50% Formamide, 0.5% SDS, 5x SSC, and 0.1 mg/ml salmon sperm DNA. Fragments of the human PAI-1, u-PA, t-PA, and TGF-␤ cDNA were used as probes (40). The DNA fragments were labeled by random priming using a commercially available kit (Amersham) and [ 32 P]dCTP (specific activity: 3,000 Ci/mmol).…”
Section: Northern Blottingmentioning
confidence: 99%
“…Although mean cortisol concentration was higher during low salt intake than during high salt intake and serum cortisol concentration increased with the number of PAI-1 4G alleles under high-salt conditions, there was no correlation between cortisol and PAI-1 antigen under either low-or high-salt conditions. Both Ang II (or its hexapeptide metabolite, Ang IV) and aldosterone increase PAI-1 expression in a variety of cell types, including astrocytes, 35 endothelial cells, 4 vascular smooth muscle cells, 36 proximal tubular epithelial cells, 37 and mesangial cells. 38 Systemic infusion of Ang II increases vascular, renal, and hepatic PAI-1 expression in rats, 39 whereas treatment of animals with ACE inhibitors, AT 1 receptor antagonists, or aldosterone receptor antagonists decreases tissue PAI-1 expression.…”
Section: Discussionmentioning
confidence: 99%